2022
DOI: 10.1186/s12870-022-03702-w
|View full text |Cite
|
Sign up to set email alerts
|

Maize growth response to different Bacillus strains isolated from a salt-marshland area under salinity stress

Abstract: Maize (Zea mays) growth performance has been hindered due to the high soil salinity. Salinity is one of the most severe abiotic stresses that has led to growth imbalance and profitability of harvests in arid and semi-arid regions. Plants have taken advantage of salt-tolerant bacteria as plant growth-promoters to enhance growth and reduce the adverse effects of salinity through the regulation of some biochemical, physiological, and molecular features. Preferences for non-chemical, eco-friendly, and economical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Another Actinomycete was reported to promote the growth of a halophyte using irrigation with seawater. Some biofilm-forming strains of Bacillus have been shown to enhance the growth of maize in saline conditions [82,83]. Another example is Bacillus subtilis (GB03), which was identified as a rhizosphere bacterium that stimulates growth of white clover under saline conditions [84], and which has since been renamed Bacillus amyloliquifaciens GB03 [85,86].…”
Section: Halophilic Bacteria With Pgpb Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…Another Actinomycete was reported to promote the growth of a halophyte using irrigation with seawater. Some biofilm-forming strains of Bacillus have been shown to enhance the growth of maize in saline conditions [82,83]. Another example is Bacillus subtilis (GB03), which was identified as a rhizosphere bacterium that stimulates growth of white clover under saline conditions [84], and which has since been renamed Bacillus amyloliquifaciens GB03 [85,86].…”
Section: Halophilic Bacteria With Pgpb Potentialmentioning
confidence: 99%
“…Solubilization and translocation of ions such as phosphate and iron (by siderophores) to the plant. Phosphate and iron are critical to the plant but are often in low abundance or present only in inorganic forms that must be solubilized for use by plants ( [82,83], Table 1). The plants were inoculated with the bacteria and grown under NaCl-alkali regimes.…”
mentioning
confidence: 99%
“…For instance, gyrB reveals highly similar bacterial community structure within Proteobacteria and Actinobacteria when compared with 16S, but it has merely 21.5% consistency in Firmicutes [34]. Therefore, amplicon sequence tools have been already developed for few genera that enable species-level resolution, such as rpoD amplicon methods for Pseudomonas and tuf-based methodology for Staphylococcus genus [29,37].…”
Section: Staphylococcus Andmentioning
confidence: 99%
“…Another study combined pulse field gel electrophoresis with tuf identification to successfully genotype Bacillus isolates from various environments [27]. Altogether, these studies suggested tuf as a potential phylogenetic marker among Bacillus species, and this gene has moreover been used for similar purposes in other genera [29].…”
Section: Introductionmentioning
confidence: 99%
“…Diverse members of Bacillus are involved in ecosystem functions including the degradation of soil organic matter, nitrogen cycle, carbon cycle, phosphorus solubilization, and eco-remediation of pollutants [ 8 ]. They also jointly function as plant growth promoters to alleviate abiotic stress or suppress plant pathogens [ 30 32 ]. In such scenarios, merely identifying individual taxa as Bacillus rather than individual species be insufficient for both basic science and potential microbiome engineering.…”
Section: Introductionmentioning
confidence: 99%